Mechanical Property Degradation after Corrosion of M24 High Strength Bolts - Qingwei CHEN; Dan XIE; Chenqing YANG; Qi GUO; Zhipeng WANG; Hui MA; Zeyan WU (Taiyuan Ligong Daxue xuebao, 2022)
In order to study the mechanical property degradation after corrosion, corrosion and mechanical tests were conducted on the M24 high strength bolts, which were treated with and without oil immersion. On the basis of neutral salt spray corrosion test, macro morphology of bolt corrosion products with different corrosion time was observed. It was found that the thickness of rust layer and the surface roughness of bolt increase with corrosion time. The corrosion of oil-free bolt was more serious than that of oil-immersed bolt in the early stage of corrosion, but the surface morphology was basically the same in the later stage of corrosion. Besides, the relationships of the two kinds of bolt between mass loss and corrosion time were stablish. On the basis of static tensile tests, it was found that the stiffness of bolt decreased gradually with the increase of corrosion degree. The stiffness degeneration formula was regressed. In addition, the load-displacement curves of oil-immersed and oil-free bolt were obtained at different corrosion time. With the increase of accelerated corrosion time, the yield strength and ultimate strength were found to have distinct decrease trends, but the elongation and area reduction were hardly influenced.